Activation of prophenoloxidase and hyperglycemia as indicators of microbial stress in the blue swimmer crab Portunus pelagicus. (November 2020) - Rajendran, Saravanan; Vasudevan, Sugumar
Abstract: Portunus pelagicus is exposed to different kinds of microorganisms leading to high metabolic stress that affects its life. The present study evaluates the activity of Phenoloxidase (PO), which is an enzyme that is actively involved in the activation of the immune defense system and hyperglycemia in P. pelagicus challenged with Escherichia coli and Vibrio harveyi injections. The results revealed a major impact of microbial injection on PO activity and significant variations in hemolymph glucose and CHH levels. Reduction of glucose level was observed after 24 h microbial incubation (275.26 ± 28.85 and 175.23 ± 21.70 μg/ml in V. harveyi and E. coli injected crabs, respectively). An elevated level of CHH (13.54 ± 0.55 fmol/ml) was observed in V. harveyi -injected crabs, and increased PO activity was recorded in E. coli -injected crabs. The results of the present study indicate that microbial stress leads to the activation of the defense system and hyperglycemia in P. pelagicus . Highlights: P. pelagicus is prone to microbial stress which affects its immune defense system. Elevated phenoloxidase activity was observed on E. coli and V. harveyi injections. Reduced glucose levels and increased CHH levels were witnessed in the hemolymph. Activation of the defense system and hyperglycemia upon microbial stress is proved.